(untitled) (Información, cultura y sociedad, 2016)
Relevant reading practices nowadays are framed under the paradigm of dialogic reading, giving relevance not only to reading but also the interaction among readers. One of these practices is a book club. They have been developed in Spain for thirty-five years in public libraries, bookstores, community centers, etc. Despite their long excistence in practice, empirical research on reading clubs is practically incipient. In this article we present the results of a qualitative research (open questionnaire, interviews and participant observation), in which we analyzed five aspects, in our opinion, fundamental: (1) the relevance of reading for those involved in clubs, (2) their reasons for participating in them, (3) selected readings, (4) the development of face meetings among its members, and (5) their current status and suggestions for their improvement. The final conclusion is that, today, book clubs are relevant.